Horse Ammunition. From the History of a Saddle - Sergey I. Lukyashko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. Horse ammunition was formed historically on a large geographical area. The most important component of it is a saddle. The ancient history of a saddle is not sufficiently investigated. It should be safely assumed that the oldest forms of seats appear together with the use of a horse for riding. We can confidently say that the appearance of the horsemen of the Cimmerians and Scythians in Western Asia in 8th – 7th centuries BC would not have been possible if there had been no such devices. There is a deep belief that horse riding in Western Asia arose under the Cimmerian-Scythian influence.